MEKANISME DISMISSAL DALAM KONSEP ANTI STRATEGIC LAWSUIT AGAINST PUBLIC PARTICIPATION (SLAPP) SEBAGAI PERLINDUNGAN HUKUM TERHADAP PEJUANG LINGKUNGAN HIDUP DI INDONESIA - Harry Setiawan; Mella Ismelina F. Rahayu (Jurnal Hukum Adigama, 2021)
Environmental problems in the form of environmental pollution and/or destruction have become the center of global attention, considering the complex impacts toward human beings. Everyone who fights for the right to a good and healthy environment can be considered environmental defender. Public participation is an important aspect that cannot be separated in terms of environmental protection and management as stated in the Rio Declaration. However, public participation which is taken by environmental defender in the context of fighting for the right to a good and healthy environment is vulnerable to attacks in the form of a lawsuit known as SLAPP. The originator of the term SLAPP themselves have stated that strategic legal forms often occur in the environmental realm. Legal protection in the form of law and regulations with a case dismissal mechanism is needed in order to protect environmental defender from SLAPP which could cause various kinds of losses, physically, energy, time, and economically. UUPPLH as the law for the environmental sector in Indonesia has regulated legal protection for everyone who fights for substantive rights in the form of a good and healthy environment, where these rights have even been recognized and guaranteed by the constitution (UUD 1945). Therefore, dismissing the case (dismissal) as early as possible against SLAPP is considered important to protect environmental defender who takes the form of public participation in carrying out their work as the guardian of environmental rights.